Structural and regulatory determinants of flagellar motility in Rhodobacterales - The archetypal flagellum of Phaeobacter inhibens DSM 17395 - Tomasch, Jürgen; Bartling, Pascal; Vollmers, John; Wöhlbrand, Lars; Jarek, Michael; Rohde, Manfred; Brinkmann, Henner; Freese, Heike M; Rabus, Ralf; Petersen, Jörn (bioRxiv, 2025)
Flagellar motility is crucial for the swim-and-stick lifestyle of Rhodobacterales and plays an important role for bacterial-algal interactions. This alphaproteobacterial order contains three distinct types of flagellar gene clusters (FGCs) for the formation of a functional flagellum. Our phylogenetically broad taxon sampling of more than 300 genomes revealed that the most common FGC, the fla1-type, was probably already present in the common ancestor of Rhodobacterales and was strictly vertically inherited, while the other two FGC types, fla2 and fla3, were spread via horizontal operon transfers. Swimming of the marine model organism Phaeobacter inhibens DSM 17395 (Roseobacteraceae) is mediated by the archetypal fla1-type flagellum. Screening of 13,000 transposon mutants of P. inhibens on soft agar plates revealed that 40 genes, including four genes encoding conserved but not yet characterized proteins (CP1-4) within the FGC, are essential for motility. Exoproteome analyses indicated that CP1-4 are required at different stages of flagellar assembly. Only eight genes outside the FGC were identified as essential for swimming motility, including all three genes of the CtrA phosphorelay. Using comparative transcriptomics of ΔcckA, ΔchpT and ΔctrA mutants of the distantly related model organisms P. inhibens and Dinoroseobacter shibae DFL 12, we identified genes for the flagellum and cyclic di-GMP turnover as core targets of the CtrA phosphorelay and a conserved connection with quorum sensing across members of the Rhodobacterales.